Investigation of natural gas hydrate slurry flow properties and flow patterns using a high pressure flow loop. (2nd June 2016) - Ding, Lin; Shi, Bohui; Lv, Xiaofang; Liu, Yang; Wu, Haihao; Wang, Wei; Gong, Jing
Abstract: The formation and agglomeration of hydrates have been a major hazard to the operating safety of deep-sea oil/gas transportation pipeline. Although many studies have been conducted to investigate the hydrates formation and particle behaviors during the transportation, studies on the gas–slurry flow properties and effects of hydrates on multiphase flow patterns are still almost blank. In this work, a series of experiments were conducted in a high pressure flow loop, using the materials of a pseudo single-liquid-phase (saturated water/oil emulsion) and a gas–liquid multiphase, respectively. It was found that hydrates agglomeration was more violent and the flow property was worse in the gas–liquid multiphase system. When hydrates formed in the gas–liquid multiphase system, the liquid flow rate would decrease in all experimental conditions while the gas flow rate showed three different changing types: decreasing, increasing or keeping constant. These changes of the flow rate would further induce a transition of the gas–liquid multiphase flow pattern in the loop. Based on the experimental data, two flow pattern maps were made. One involved the effects of hydrates while the other did not. Through the comparison between the two flow pattern maps, it is confirmed that the influence of hydrates on the flow pattern is significant. The differences between the two flow pattern maps were also analyzed using a flow pattern transition model to provide an insight into the mechanism of how hydrates affect the multiphase flow pattern. Highlights: Hydrates aggregation is especially violent and rapid in multiphase system. Hydrates formation will cause gas/liquid flow rate to change in different ways. Three distinctions are found from flow pattern maps with/without hydrates. Mechanism of how hydrates affect flow pattern transition is developed.